2018
DOI: 10.1186/s12888-018-1890-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-traumatic stress disorder, acute stress disorder and depression following violence related injury treated at the emergency department: a systematic review

Abstract: BackgroundIn order to gain insight into the health impact of violence related injury, the psychological consequences should be taken into account. There has been uncertainty regarding the prevalence of posttraumatic stress disorder (PTSD), acute stress disorder (ASD), and depression among patients with violence related injury. An overview of prevalence rates may inform our understanding of both prognosis and recovery for these patients. Therefore, we aim to provide an overview of the published literature repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
7
22
0
Order By: Relevance
“…It is important to note that in the present study, PTSD after assault showed a higher impact on the four cluster symptoms of intrusion, avoidance, negative mood alterations and arousal. Our finding is in agreement with a recent systematic review focused on PTSD following violence-related injury and reported a wide range of prevalence [ 29 ]. The current literature suggests that assault victims are at higher risk of developing psychological illness and PTSD [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note that in the present study, PTSD after assault showed a higher impact on the four cluster symptoms of intrusion, avoidance, negative mood alterations and arousal. Our finding is in agreement with a recent systematic review focused on PTSD following violence-related injury and reported a wide range of prevalence [ 29 ]. The current literature suggests that assault victims are at higher risk of developing psychological illness and PTSD [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…This might reflect sampling and recording biases as the users were self-selected and responsible for recording symptoms. The means of eliciting responses in symptom studies can significantly impact estimated prevalence thus making comparison between studies difficult [ 25 27 ]. Symptom prevalence studies are also complicated by adjusting for background prevalence as well as varying definitions of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Greene et al showed that 2 to 15% of individuals in the general population suffered from PTSD, regardless of the trauma [ 5 ]. In a meta-analysis, Ophuis et al identified post-traumatic stress one year after any physical trauma in 16 to 27% of victims [ 22 ]. Qureshi et al found PTSD in 21% of patients 18 months after a head injury [ 23 ].…”
Section: Discussionmentioning
confidence: 99%